University Lecturers and Students Preparedness for Online Teaching and Learning in Zimbabwe - Muchemwa, Stella (G-Card, 2022)
The outbreak of COVID 19, which disrupted the normal lecture delivery system in universities, profoundly impacted Zimbabwe as a nation. This study investigated on university lecturers and students’ preparedness to online teaching and learning at the outbreak of COVID 19 in the country. The study also looked at how these two groups adjusted and what still need to be done to effect e-learning. The researcher carried out massive interviews to both lecturers and students. The study employed the thematic data processing approach. Findings showed that university lecturers and students were caught unaware and unprepared for alternative learning modes though they did their best to rise above the challenges. Lecturers from very few well-to-do universities got either or both data bundles and gadgets. Universities experienced the following challenges: limited accessibility to internet, limited mobile networks, unreliable electricity supply, lack of appropriate technological gadgets, lack of technical know-how, high levels of stress and low performance level for both lecturers and students. The study concluded that the e-learning that was introduced as a mitigating measure, left a lot to be desired and this needs to be ‘fixed’ in preparation for future similar calamities and general technological advancement. The study recommended national and university funding of necessary electronic gadgets, e-learning infrastructure and data bundles for smooth running of e-learning programs.